Nanocomposites based on Resole/graphene/carbon fibers: A review study - Chou Yi Hsu; Zaid H. Mahmoud; Sherzod Abdullaev; Bahira Abdulrazzaq Mohammed; Usama S. Altimari; Murtadha Laftah Shaghnab; Ehsan kianfar; Ghassan Fadhil Smaisim (Case Studies in Chemical and Environmental Engineering, 2023)
In this Review, Phenolic resins have excellent dimensional, thermal, chemical and corrosion resistance. Also, the volatile substances produced during the thermal degradation of this resin have low toxicity and, in addition, they have high charring. Phenolic resins have been applied in many areas such as internal parts of war planes, structures used in marine platforms, flame retardant plastics and carbon/carbon composites due to having the mentioned favorable properties. In this article, phenolic resin samples of Resole reinforced with carbon fibers and graphene nanoparticles were prepared. In the last decade, the development of new polymer nanocomposites has grown significantly. In contrast to conventional and common composites, nanocomposites have a feature in which a filler that has a size of less than 100 nm in at least one dimension is used. One of the advantages of polymer nanocomposites is that it gives several properties to the primary polymer, despite the fact that it creates less limitations in its processability than other reinforcements. The key to these features is in the design and behavior of polymer nanocomposites, which includes the size and properties of the filler nanoparticle and the interface between the filler nanoparticle and the matrix. Nowadays, in many engineering applications, it is necessary to combine the properties of materials, and it is not possible to use one type of material that satisfies all the desired properties. For example, in the aerospace industry, there is a need for materials that have high strength, lightness, wear resistance and good resistance to ultraviolet light and do not lose their strength at high temperatures. Since it is difficult to find a material that has all the above properties, it is better to look for a method to combine the properties of the materials, this solution is the use of composite materials.